FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) PADA PASANGAN USIA SUBUR(PUS) DI KELURAHAN TEMBILAHAN KOTA WILAYAH KERJA PUSKESMAS TEMBILAHAN KOTAKECAMATAN TEMBILAHAN - Haryati Astuti (Jurnal Kesehatan Husada Gemilang, 2018)
Indonesia is a develop country with a high population growth rate. The result of Statistic Center survey on August 2010 showed the number of Indonesian people were 237.556.363 people, with its growth rate 1.49% a year. Accordingly there was always an effort which was addressed by birth control program. The IUD is a device to be put in a female’s womb in order to get a long term contraception. This research aimed at identifying the factors relate to the use of IUD in couples of reproductive age at Community Health Center of Tembilahan Kota. This research was a descriptive analytic study with cross-sectional approach. The number of samples in this study were 73 respondents of 8507 EFA with precision of 75%. The sample was taken through questionnaire, where the data gained by having interviews on the birth control acceptors, with purposive sampling technique. On the result of statistical analysis, there is a correlation between knowledge and the use of IUD (p = 0,005), there is a correlation between education and the use of IUD (p= 0,048), there is a correlation between attitude and the use of IUD (p= 0,024), there is a correlation between age and the use of IUD (p= 0,028), there is a correlation between financial income and the use of IUD (p = 0,047), there is a correlation between parity and the use of IUD (p = 0,604). The result of this research is recommended to related stakeholders and cross sectoral stakeholders (TNI, PKK and IBI) to increase the socialization and empowerment up to district level by building a village of birth control with continuous program and empowerment. So, the EFA comprehend the birth control especially MKJP can be increased. It is expected that couples of reproductive age would use.